Thermally Induced Intramolecular Benzannulation of Diazoacetoacetate Enones Tethered with Unactivated Alkynes: Synthesis of Substituted 6H-Benzo[c]chromenes - Chen, Yangfan; Wu, Di; Zhou, Jiawen; Wang, Yun; Huang, Jing; Xu, Xichen (Synthesis, 2019)
A facile and efficient intramolecular benzannulation strategy for the synthesis of substituted 6H-benzo[c]chromenes from diazoacetoacetate enones tethered with unactivated alkynes has been developed. The reaction proceeds in moderate to good yields under operationally simple conditions with thermally induced [4+2]-annulation of intermediate vinyl ketenes as the key step.
Keywords: vinyl ketene; Wolff rearrangement; benzannulation; 6H-benzo[c]chromene; diazoacetoacetate enone